Korban Sebagai Pembentuk Kejahatan Tindak Pidana Perdagangan Orang Di Masyarakat Perbatasan Kalimantan Barat - Abunawas, Abunawas (Lex Librum : Jurnal Ilmu Hukum, 2023)
Abstract In general, this study aims to further understand the role of victims (Typology of Victim Precipitation) in realizing the crime of trafficking in persons in border communities, and the elaboration of this understanding will be elaborated in an advanced understanding of aspects of legal policy in protecting and preventing victims from becoming victim precipitation in border communities. West Kalimantan. The use of research method in this study uses a normative-empirical, supported by a qualitative approach so that in the end, the analysis results are obtained by describing the results of research on the typology of victims and policies in protecting and trying to prevent victim precipitation in the crime of trafficking in persons in the border communities of West Kalimantan. Keywords: Victims, Trafficking in Persons, Communities, Borders